Between the tradition and legal regulation – the analysis of the attitude of the President of the Russian Federation Towards the Russian Orthodox Church in 2012–2022 - Stępień, Jakub (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Relations between representatives of state authorities and religious communities remain an important element of current political and social reality of most countries of Central and Eastern Europe. Attempts to use the social authority of religious organizations in order to gain or strengthen their position are undertaken by politicians in various forms and in a heterogeneous scope. Such activity often deviates from the standards set by the content of the constitutions of these countries. This type of phenomenon is also noticeable in the case of President Vladimir Putin’s activities towards the Russian Orthodox Church, which – while remaining strongly inspired by the tradition of the Church’s dependence on the political power of the Russian state – violates the provisions of the Constitution and Federal Laws of the Russian Federation in the field of relations between the state and religious communities.